Hemodynamic markers of pulmonary vasculopathy for prediction of early right heart failure and mortality after heart transplantation - Rieth, Andreas; Rivinius, Rasmus; Lühring, Tom; Grün, Dimitri; Keller, Till; Grinninger, Carola; Schüttler, Dominik; Bara, Christoph L.; Helmschrott, Matthias; Frey, Norbert; Sandhaus, Tim; Schulze, Christian; et al. (The journal of heart and lung transplantation, 2023)
Background - Elevated pulmonary vascular resistance (PVR) is broadly accepted as an imminent risk factor for mortality after heart transplantation (HTx). However, no current HTx recipient risk score includes PVR or other hemodynamic parameters. This study examined the utility of various hemodynamic parameters for risk stratification in a contemporary HTx population. - Methods - Patients from seven German HTx centers undergoing HTx between 2011 and 2015 were included retrospectively. Established risk factors and complete hemodynamic datasets before HTx were analyzed. Outcome measures were overall all-cause mortality, 12-month mortality, and right heart failure (RHF) after HTx. - Results - The final analysis included 333 patients (28% female) with a median age of 54 (IQR 46-60) years. The median mean pulmonary artery pressure was 30 (IQR 23-38) mm Hg, transpulmonary gradient 8 (IQR 5-10) mm Hg, and PVR 2.1 (IQR 1.5-2.9) Wood units. Overall mortality was 35.7%, 12-month mortality was 23.7%, and the incidence of early RHF was 22.8%, which was significantly associated with overall mortality (log-rank HR 4.11, 95% CI 2.47-6.84; log-rank p < .0001). Pulmonary arterial elastance (Ea) was associated with overall mortality (HR 1.74, 95% CI 1.25-2.30; p < .001) independent of other non-hemodynamic risk factors. Ea values below a calculated cutoff represented a significantly reduced mortality risk (HR 0.38, 95% CI 0.19-0.76; p < .0001). PVR with the established cutoff of 3.0 WU was not significant. Ea was also significantly associated with 12-month mortality and RHF. - Conclusions - Ea showed a strong impact on post-transplant mortality and RHF and should become part of the routine hemodynamic evaluation in HTx candidates.